Fibrous Periodontitis: Modern Evidence-Based Approaches to Treatment - Raxmonova, Shoxsanam (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
Fibrous periodontitis is a chronic form of periodontal inflammation characterized by productive changes and the formation of connective tissue structures. The condition often remains asymptomatic and is detected mainly during radiographic examination, which complicates timely diagnosis. This work aims to systematize current treatment approaches and identify the most effective methods based on evidence-based dentistry. A review of recent domestic and international studies demonstrated that endodontic therapy remains the fundamental strategy, with mechanical and pharmacological root canal treatment combined with sodium hypochlorite or chlorhexidine irrigation achieving clinical success rates of 85–92%. The use of calcium hydroxide–based medicaments increases stable remission up to 95%. Adjuvant physiotherapy methods, such as laser therapy and ultrasonic irrigation activation, enhance canal sterility and accelerate reparative processes by 20–25%. In resistant cases, surgical interventions (apicoectomy, hemisection, root resection) are indicated, ensuring long-term tooth preservation in 70–80% of patients. A comprehensive, individualized, and multi-stage approach is therefore essential to improving the prognosis and quality of dental care in fibrous periodontitis.